Verrucous Spitz Nevus in a Japanese Female - Rie Honda; Yuka Iino; Shusaku Ito; Masaru Tanaka (Karger Publishers, 2013)
A 23-year-old female presented with a reddish-brown dome-shaped hyperkeratotic nodule of 11 × 10 mm on the left lower leg. Dermoscopic examination demonstrated a prominent whitish scaly area with ring-like appearance, pinkish-white structureless areas, a few milia-like cysts, dotted and glomerular vessels, and light brown globules. The lesion was completely excised under the diagnosis of verruca vulgaris or dermatofibroma. Histopathological examination revealed a well-circumscribed symmetric lesion with hyperkeratosis, acanthosis, and pseudohorn cysts. The lesion was composed of spindle-shaped and epithelioid melanocytes with large cytoplasm arranged in confluent nests surrounded by stromal fibrosis. Mitotic figures and Kamino bodies were absent. Moderate proliferation of capillaries was found in the papillary dermis. Immunohistochemical staining with melan-A or S-100 was positive for tumor cells, but the staining with HMB-45 was negative. Melan-A staining was weaker in the deeply situated cells than in the superficial ones, which is known as stratification. Finally, we made a diagnosis of verrucous Spitz nevus based on these findings. We should have been aware of the entity of verrucous Spitz nevus as a variant of Spitz nevus and its dermoscopic features in order to reach a correct diagnosis before excision.